2012
DOI: 10.1002/mus.23347
|View full text |Cite
|
Sign up to set email alerts
|

Decay‐accelerating factor 1 deficiency exacerbates Trypanosoma cruzi‐induced murine chronic myositis

Abstract: Introduction: Murine infection with Trypanosoma cruzi (Tc) has been used to study the role of T‐cells in the pathogenesis of human inflammatory idiopathic myositis. Absence of decay‐accelerating factor 1 (Daf1) has been shown to enhance murine T‐cell responses and autoimmunity. Methods: To determine whether Daf1 deficiency can exacerbate Tc‐induced myositis, C57BL/6 DAF+/+ and DAF−/− mice were inoculated with 5 × 104 trypomastigotes, and their morbidity, parasitemia, parasite burden, histopathology, and T‐cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…In comparison with WT, in previous studies, Daf1 −/− mice have shown higher acute viral load in murine CMV [32] but lower viral load in acute and chronic LCMV infection [33] or bacteremia after Pneumococcal pneumonia infection [34]. Reduced parasite load was also found in chronic Trypanosome cruzi -infected mice [35]. It is not clear why Daf1 −/− mice showed an early drop in survival and a higher bacterial burden at the start of the leptospiruric phase.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In comparison with WT, in previous studies, Daf1 −/− mice have shown higher acute viral load in murine CMV [32] but lower viral load in acute and chronic LCMV infection [33] or bacteremia after Pneumococcal pneumonia infection [34]. Reduced parasite load was also found in chronic Trypanosome cruzi -infected mice [35]. It is not clear why Daf1 −/− mice showed an early drop in survival and a higher bacterial burden at the start of the leptospiruric phase.…”
Section: Discussionmentioning
confidence: 88%
“…Standard cDNA samples with 10-fold serial dilutions were used for PCR efficiency calculations. Cycle threshold (Ct) values were obtained for each individual reaction, and the Ct of the host-expressed β-actin was subtracted to obtain pro-collagen type I, SMA, Gal-3, TGF-β1, IL-4, IL-10, IL-12, IL-13, IL-17 and IFN-γ normalized values, respectively [35], [43]. To obtain bacterial burden values, 16SDNA bacterial gene was amplified and the number of bacteria was referred to that of the host cells [35].…”
Section: Methodsmentioning
confidence: 99%
“…Evaluation of the tissue specimens was performed by light microscopy by a researcher blinded to the treatment assignment. Presence of amastigote nests was recorded and the degree of myocardial and skeletal inflammation was scored as described previously [15,16].…”
Section: Tissue Sample Preparation and Histological Evaluationmentioning
confidence: 99%
“…The same authors found calcifications in the skeletal muscle studied, but they studied the rectus abdominis muscle. A recent study reports the presence of skeletal muscle fibers undergoing calcification and necrosis as a consequence of T. cruzi II infection in WT and Daf1-deficient mice [37]. There is another report that superficially mentions muscular calcification as a consequence of T. cruzi infection, but that study was achieved using also a genotype II strain [38].…”
Section: Discussionmentioning
confidence: 99%